Influence of Green Supply Chain Practices on Performance of Selected County Governments in Kenya's Lake Region Economic Block - Agong, Judith Achieng; Mogaka, Conrad (International Journal of Supply Chain and Logistics, 2025)
Purpose: The study focuses on determining the influence of green supply chain practices on Performance of selected County Governments in Lake Nyanza Region. The specific objectives of the study were as indicated below;-to establish the influence of green procurement, sustainable logistics, waste disposal and eco design practices on Performance of selected County Governments in Kenya. Methodology: The unit of analysis was six Counties in Lake Nyanza Region. The study targeted 120 employees. The unit of observation was procurement, and supply chain specialist in the six Counties. The study employed the Israel (2010) formula to get a sample size of 92 respondents. The questionnaire was administered by dropping and picking. Findings: The analysis reveals that all four green supply chain practices positively influence the performance of County Governments. Specifically, sustainable logistics was found to have the most substantial impact, followed by eco design, green procurement, and waste disposal. These practices contribute to improved operational efficiency, cost reduction, environmental sustainability, and enhanced service delivery. The study concludes that the adoption of green supply chain practices is crucial for improving the overall performance of County Governments in Kenya. Unique Contribution to Theory, Policy and Practice: This research provides valuable insights into how County Governments can enhance their performance by integrating sustainability into their supply chain practices, thereby contributing to more effective and responsible governance. Recommendations include the development of clear green procurement policies, investment in sustainable logistics systems, enhanced waste management frameworks, and the promotion of eco design in procurement planning. Furthermore, the study suggests areas for further research, such as exploring the barriers to implementing green practices and conducting longitudinal studies to assess their long-term impact.